NOTES TO THE LIFE AND WORK OF NIKOLAY LUKASHOV - Gulbahor Saidganieva (Galaxy International Interdisciplinary Research Journal, 2021)
In the last quarter of the last century, in Kokand, along with Uzbek, Russian-language literature developed rapidly, in which the purest, highest ideals of a person were sincerely revealed. The main character of the poems created by the poets was a simple working people,the landscapes of Kokand and nearby villages, the character of ordinary people, the relationship between them, picturesque pictures of their lives. This is the main content of the work of the Russian-speaking writers of Kokand, such as Leonid Solovyov, Boris Parmuzin, Nikolai Lukashov, Mikhail Charny, Ilmer Nazarov and others. Kokand literature developed in line with the republican literary process, embodying the best creative tendencies. A special place among the Kokand lyricists was occupied by the poet Nikolai Lukashov.